HUBUNGAN CINA DENGAN BARAT - Agus Rustamana; Ari Baitul Maisah; Ahmad Muhammad Bustomi; Tarra Aulia Mulyana (Sindoro: Cendikia Pendidikan, 2023)
This research aims to describe the influence of the opium war on China in the sociocultural and economic aspects. This research uses historical methods, namely Heuristics, source criticism, verification, and historiography. The results of this study indicate that: (1) The opium trade cannot be separated from the arrival of Arab and Turkish traders who obtained opium from the Middle East and India in the 7th century; (2) The opium trade, which was managed by the local government as well as during the Dutch East Indies period, affected the social life of the community, especially disputes between the community and the Dutch East Indies government; The opium war had a great impact or influence on the Chinese people, the positive impact felt by the Chinese people was the emergence of a sense of nationalism as a result of the treaties that harmed them so that they made anti-Western movements. While the negative impact felt by the community is the decline in the level of people's welfare, and the emergence of economic and social crises.